Pengaruh celebrity endorser Fadil Jaidi dalam social media marketing terhadap brand awareness pada bumame farmasi di Kota Jakarta - Denise Mayliana Sari; Trisha Gilang Saraswati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Since the COVID-19 pandemic outbreak entered Indonesia, many companies have taken advantage of business opportunities in the pharmaceutical industry, especially in the field of COVID-19 test services. PT Budimanmaju Megah Farmasi or Bumame Farmasi is one of the companies that provides COVID-19 test services that utilize social media to market and promote their services. Bumame Farmasi utilizes social media marketing with the help of celebrity endorsers such as Fadil Jaidi to build a Bumame Farmasi brand awareness in Jakarta. In this study was conducted with the aim of knowing how much influence given by celebrity endorser Fadil Jaidi to Brand Awareness on Bumame Pharmacy in Jakarta. The population used in the study was Instagram social media follower Fadil Jaidi who knew Bumame Pharmaceuticals and used quantitative methods with 385 respondents who participated in filling out questionnaires through online media selected through simple random sampling or probability sampling. The analytical techniques used are descriptive analysis methods and multiple linear regression analysis. Based on the results of the study can be concluded that there is a partial influence on the variables trustworthiness, expertise, attractiveness, respect, and similarity to brand awareness variables simultaneously and partially. Partially the influence of trustworthiness variables by 14%, expertise variables by 18%, attractiveness influence by 5.4%, respect variables by 2.6% and similarity variables by 27% to Bumame Pharmaceutical brand awareness in Jakarta City. The simultaneous influence on variable trustworthiness, expertise, attractiveness, respect, and similarity to brand awareness in the city of Jakarta by 67% while 33% is the influence of other factors that are not studied.